2020
DOI: 10.35848/1882-0786/abb68d
|View full text |Cite
|
Sign up to set email alerts
|

Frequency dependence dielectrophoresis technique for bridging graphene nanoribbons

Abstract: We succeeded in bridging unzipped graphene nanoribbons (GNRs) and separating them from unwanted single-walled carbon nanotubes (SWNTs) using a frequency-dependent dielectrophoresis (DEP) method by varying the frequency and applied voltage used for future assembly. Atomic force micrographs and Raman spectra proved that unzipped GNRs were successfully bridged by the DEP method at frequencies higher than 13 MHz. The theoretical calculation also supported the finding that only GNRs were collected from a mixture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…The chemical vapor deposition (CVD) synthesized SWNT (SigmaAldrich) with (6, 5) chirality and 0.7-0.9 nm diameter was purified by annealing at 200 °C for 20 h, followed by refluxing in concentrated HCl (12 M) at 110 °C for 1 h, to remove the amorphous carbon and Fe catalysts 31,45 . The acid treated SWNT was filtered and washed with deionized water to pH 7 prior to drying at 80 °C to obtain the purified SWNT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical vapor deposition (CVD) synthesized SWNT (SigmaAldrich) with (6, 5) chirality and 0.7-0.9 nm diameter was purified by annealing at 200 °C for 20 h, followed by refluxing in concentrated HCl (12 M) at 110 °C for 1 h, to remove the amorphous carbon and Fe catalysts 31,45 . The acid treated SWNT was filtered and washed with deionized water to pH 7 prior to drying at 80 °C to obtain the purified SWNT.…”
Section: Methodsmentioning
confidence: 99%
“…Chemical vapor deposition (CVD) synthesized SWNTs (Sigma-Aldrich) with (6, 5) chirality and 0.7-0.9 nm diameter were purified by annealing at 200 °C for 20 h, followed by refluxing in concentrated HCl (12 M) at 110 °C for 1 h to remove the amorphous carbon and Fe catalysts. 31,45 The acid treated SWNTs were filtered and washed with deionized water to achieve a pH value of 7 prior to drying at 80 °C to obtain the purified SWNTs. Phosphomolybdic acid hydrate (H 3 PMo 12 O 40 •12H 2 O, PMo 12 hereafter) (Sigma-Aldrich), isopropyl alcohol (IPA) (Wako), acetone (Wako), acetonitrile (Wako), and commercially available Gekiochi melamine sponge (LEC, Inc.) were used as purchased.…”
Section: Methodsmentioning
confidence: 99%
“…The CNTs do not bridge across the electrode if the AC electric signal has a frequency outside this range. The lower limit is defined as the frequency at which other forces dominate the DEP force [124]. While the upper limit is the frequency at which the charge is unable to dipole with the AC switching time.…”
Section: Dielectrophoresis Parametersmentioning
confidence: 99%
“…[21] We have recently found that the unzipping of double-walled carbon nanotubes (DWNTs), rather than single-or multi-walled, results in high-yield production of crystalline single-layered GNRs (sGNRs) with a relatively short sonication time (e.g., 20 h for SWNTs and 5 h for DWNTs), in which poly(m-phenylenevinylene-co-2,5-dioctoxy-pphenylenevinylene) (PmPV) acts as both an efficient dispersing agent and radical sources. [20,22,23] Regarding the mechanism of DWNT unzipping, it is observed from atomic force microscopy (AFM) that double-layered GNRs (dGNRs) are first generated, with subsequent sonication leading to the separation of the two graphene layers to form sGNRs. Complementary evidence of this can be found from the presence of partially branched intermediate state GNRs (i.e., y-shaped GNRs) at an early reaction stage (sonication time ≈1 h).…”
Section: Introductionmentioning
confidence: 99%